2008
DOI: 10.1002/anie.200705229
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of Substituted γ‐Lactams from Acylsilanes

Abstract: It takes three: The stereoselective synthesis of highly substituted γ‐lactams from amide enolates, acylsilanes, and imines is reported. This multicomponent reaction accesses γ‐amino‐β‐hydroxy amides in a single flask with good yields and excellent levels of diastereoselectivity (see scheme). Exposure of the linear products to microwave irradiation and acidic conditions promotes a cyclization to form the corresponding γ‐lactams in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 47 publications
0
13
0
2
Order By: Relevance
“…[1] For example,c hiral a-hydroxysilanes (= a-silyl alcohols) and their derivatives have been utilized in stereocontrolled CÀC bond formation and rearrangements. [5] These processes do provide access to enantioenriched secondary a-silyl alcohols but the reductions are not applicable to tertiary systems.Hence,the construction of chiral tertiary a-silyl alcohols remains challenging.T he most straightforward way of preparing them would be the enantioselective addition of carbon nucleophiles to acylsilanes, [6,7] and several advances have been disclosed recently. [5] These processes do provide access to enantioenriched secondary a-silyl alcohols but the reductions are not applicable to tertiary systems.Hence,the construction of chiral tertiary a-silyl alcohols remains challenging.T he most straightforward way of preparing them would be the enantioselective addition of carbon nucleophiles to acylsilanes, [6,7] and several advances have been disclosed recently.…”
mentioning
confidence: 99%
“…[1] For example,c hiral a-hydroxysilanes (= a-silyl alcohols) and their derivatives have been utilized in stereocontrolled CÀC bond formation and rearrangements. [5] These processes do provide access to enantioenriched secondary a-silyl alcohols but the reductions are not applicable to tertiary systems.Hence,the construction of chiral tertiary a-silyl alcohols remains challenging.T he most straightforward way of preparing them would be the enantioselective addition of carbon nucleophiles to acylsilanes, [6,7] and several advances have been disclosed recently. [5] These processes do provide access to enantioenriched secondary a-silyl alcohols but the reductions are not applicable to tertiary systems.Hence,the construction of chiral tertiary a-silyl alcohols remains challenging.T he most straightforward way of preparing them would be the enantioselective addition of carbon nucleophiles to acylsilanes, [6,7] and several advances have been disclosed recently.…”
mentioning
confidence: 99%
“…Because of their interesting biological activities, their widespread occurrence in many natural products [ 28 ], and their broad synthetic utility, γ-lactam ring systems have received considerable attention in organic chemistry. Recent strategies toward the construction of the γ-lactam motif comprise β-lactam to γ-lactam ring expansions [ 29 30 ], aziridine ring openings followed by cyclization with enolates [ 31 ], palladium-catalyzed cyclizations [ 32 ], cycloadditions [ 33 ], multicomponent reactions [ 34 ], and even NHC catalysis [ 35 36 ]. Nevertheless, the methodology developed by Rovis indisputably represents an important breakthrough, providing an elegant alternative access to trans -γ-lactams in a highly enantio- and diastereoselective way.…”
Section: Discussionmentioning
confidence: 99%
“…The unconventional nucleophilic species 77 subsequently underwent addition to an imine to provide the corresponding g-amino-b-hydroxy amide in a onepot reaction with a good yield and a high level of diastereoselectivity of up to 86% de, as shown in Scheme 1.134. 222 The authors have demonstrated that the subsequent exposure of this g-amino-b-hydroxy amide to microwave irradiation and acidic conditions promoted a cyclisation to form the corresponding g-lactam in high enantiomeric excesses of 87% ee (Scheme 1.134). Given that a wide number of biologically active products include g-lactam moieties, the importance of this novel methodology, allowing chiral highly substituted g-lactams to be achieved, was demonstrated.…”
Section: Multicomponent Reactions Based On the Petasis Reactionmentioning
confidence: 99%